Impact of Health Educational Program Upon Nurses' Knowledge Towards Postoperative Wounds Care In Mosul Teaching Hospitals - hussien, Tahsein; Jaddoue, Batool (Iraqi National Journal of Nursing Specialties, 2018)
Objectives: The study aimed to assess the needs of nurses' knowledge toward post operative wound care and to constructed health educational program upon nurses who are working in surgical wards, to determine the relation between nurses' knowledge and their demographical characteristic which includes ( age, gender, level of education, number of years experience in the surgical wards, years of experience in nursing service, and number of attending an educational sessions), and to identify the impact of the health educational program on their knowledge through perform post-test every two months after implementation of the program for six months consequences. Methods: A quasi- experimental study was conducted in Al-Jamhuree Teaching Hospital and Al- Salam Teaching Hospital in Nineveh governorate during the period from 10th September 2013 up to 10th March 2014. To fill full the objective of the study a purposive sample (non probability) consists of (60) nurses, the sample divided into tow equal groups (study and control groups), the study group are exposed to the educational program. The knowledge questionnaire test was conducted to measure the impact of the program, which consists of (63) multiple choice questions regarded to post operative wound care. Data were collected through the use knowledge questionnaire test which is related to nurses' knowledge test, which were developed to achieve the purpose of the study. Reliability of the instrument was determined through the use of test- retest approach. While the Instrument validity was determined through content validity, by a panel of experts. Results: The results that the nursing in the study group are benefited from the implementation of the health education program and it was a great effect on developing and improved their knowledge regarded all parts of knowledge tests related to post operative wound care. Recommendations: Based on the results of the current study the researcher recommended the followings: Based on analysis of the results, It is necessary to develop a continuous, periodic in-service educational and training programs should be utilize for all surgical nursing especially for newly jointed nurses to enhance their ability in dealing with surgical wound in order to improve the quality of care, and Benefit from the present program by coping it in a form of a manual to be distributions for using it.